2021
DOI: 10.3390/ijms22094463
|View full text |Cite
|
Sign up to set email alerts
|

A Role for TGFβ Signaling in Preclinical Osteolytic Estrogen Receptor-Positive Breast Cancer Bone Metastases Progression

Abstract: While tumoral Smad-mediated transforming growth factor β (TGFβ) signaling drives osteolytic estrogen receptor α-negative (ER-) breast cancer bone metastases (BMETs) in preclinical models, its role in ER+ BMETs, representing the majority of clinical BMETs, has not been documented. Experiments were undertaken to examine Smad-mediated TGFβ signaling in human ER+ cells and bone-tropic behavior following intracardiac inoculation of estrogen (E2)-supplemented female nude mice. While all ER+ tumor cells tested (ZR-75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 82 publications
(177 reference statements)
0
5
0
Order By: Relevance
“…However, analysis of clinical series looking at disseminated tumors cells in bone marrow suggests that the longer a woman is post-menopausal, the less attractive bone microenvironment is for tumor cells [62,63]. A recent study has shown that estradiol and TGF-β upregulate PTHrP in ER+ osteotropic BCa cells [64] and increase the progression of osteolytic metastases in ER-negative BCa cells [65]. Therefore, estrogen deficiency may contribute to the benefit of adjuvant BPs in bone recurrence in post-menopausal women, while in metastatic settings, the menopausal status does not affect outcomes related to BTAs [66].…”
Section: Bone Pre-metastatic Nichementioning
confidence: 99%
“…However, analysis of clinical series looking at disseminated tumors cells in bone marrow suggests that the longer a woman is post-menopausal, the less attractive bone microenvironment is for tumor cells [62,63]. A recent study has shown that estradiol and TGF-β upregulate PTHrP in ER+ osteotropic BCa cells [64] and increase the progression of osteolytic metastases in ER-negative BCa cells [65]. Therefore, estrogen deficiency may contribute to the benefit of adjuvant BPs in bone recurrence in post-menopausal women, while in metastatic settings, the menopausal status does not affect outcomes related to BTAs [66].…”
Section: Bone Pre-metastatic Nichementioning
confidence: 99%
“… 157 In an estradiol-dependent ER+ BCBM mouse model, Erα increased the production of the tumor osteolytic factor parathyroid hormone-related protein, the number of osteoclasts at the bone–tumor interface, and osteolytic bone damage in an estradiol-dependent manner, which explains the propensity of ER+ tumors to develop osteolytic pathologies. 158 Considering the risk of bone metastasis in ER-overexpressing BC, augmenting ER-targeted therapy may provide new treatment avenues for this BC subtype and improve survival.…”
Section: Therapeutic Nps Against Er-positive Bcbmmentioning
confidence: 99%
“…TGF-β is produced by active osteoclasts and increases the production of PTHrP. The research on samples of MDA-MB-231 breast cancer cells with neutralized TGF-β shows a significant decrease in osteolytic lesions [ 112 ].…”
Section: Molecular Basis Of Spine Metastasesmentioning
confidence: 99%